Anomalous superficial ulnar artery based flap - Ramani, C. V. (Medknow Publications & Media Pvt Ltd, 2014)
Upper limb shows a large number of arterial variations. This case report describes the presence of additional superficial ulnar artery which was used to raise a pedicle flap to cover an arm defect thus avoided using the main vessel of the forearm - radial or ulnar artery. Vascular anomalies occurring in the arm and forearm tend to increase the likelihood of damaging the superficial anomalous arteries during surgery. Superficial ulnar or radial arteries have been described to originate from the upper third of the brachial artery; here we report the origin of the anomalous superficial ulnar artery originating from the brachial artery at the level of elbow with the concomitant presence of normal deep radial and ulnar arteries.